Torrefied wood effects on the seedling quality of Zelkova serrata and Fraxinus rhynchophylla in a containerized production system. Issue 4 (2nd October 2017) - Han, Si Ho; Meng, Loth; Rahman, Afroja; Ko, Youngtak; Cho, Min Seok; Park, Byung Bae
ABSTRACT: Biochar can be used as a kind of soil amendment in crop production, but there are few studies on containerized seedling production in forestry. The purpose of this study was to investigate the amount of torrefied wood to mix with growing medium for Zelkova serrata and Fraxinus rhynchophylla seedling production in a containerized system. We used torrefied wood made from chips of Quercus accutissima, which was mixed with growing medium by 0%, 10%, 20%, 30%, and 40% in volume. We applied two levels of 0.5 g/L (1×) and 1.0 g/L (2×) commercial fertilizer for fertilization treatment. Generally, growth parameters such as height, root collar diameter, and dry weight were comparable among 0%, 10%, and 20% mixed ratios, but those at 30% and 40% mixed ratio were lower than other mixed ratios. The 2× fertilization significantly increased height by 29%, root collar diameter by 18%, total dry weight by 52%, and quality index by 31.4% compared to the 1× fertilization across mixed ratios. Our results suggest that torrefied wood can be substitutable for 20% of the growth medium in total volume in containerized Zelkova serrata and Fraxinus rhynchophylla seedling production systems.